Peningkatan Kemampuan Bahasa Inggris UMKM Pariwisata melalui Pelatihan English for Tourism di Kawasan Whale Shark Sumbawa - Muh Mahrup Zainuddin Sabri; Husaini Husaini; Ersa Anita Aulia; Ade Dwi Cahyanti; Rabiatun Adawiah (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2025)
This Community Service (PKM) activity aims to improve the English language skills of Micro, Small, and Medium Enterprises (MSMEs) operating in the tourism sector in the Whale Shark area of ​​Sumbawa. This training program is designed with a focus on mastering vocabulary and practical expressions commonly used in the context of tourism services, especially for interacting with foreign tourists. The material provided includes English for Tourism with a participatory, contextual, and applicable approach. The training method includes role-play activities, conversation simulations, and various practical exercises adapted to real-life situations in tourism activities in the Whale Shark area. During the implementation, participants were actively involved in the learning process through direct practice and group discussions. Based on the results of the evaluation, this activity showed a significant increase in the participants' self-confidence and English communication skills. Thus, this training has proven effective in helping MSMEs in tourism to be better prepared to face the global market and provide higher-quality services to foreign tourists, while also supporting the development of local tourism destinations based on foreign language competency.